Analisis Hubungan Biaya, Volume, Laba dan Titik Impas (BEP) Dalam Pengambilan Keputusan Suatu Perusahaan - Silalahi, Yeni Friska; Gurning, Juli Indah Sari; Sinaga, Frisillia Marsaulina; Manik, Lidia; Siallagan, Hamonangan (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the relationship between cost, volume, profit, and break-even point (BEP) with management decision making in a manufacturing company, a case study at PT.X. Secondary data includes sales volume, selling price, and ptoduction/non- production costs. Contribution Margin (CM), BEP, and Degree of Operating Leverage (DOL) are calculated using absorption costing and variable costing. The new policy in May 2024 (improving the quality of raw materials, selling price, advertising costs) increased sales volume to 10.000 units, resulting in a net profit of Rp. 45.000.000, with a DOL of 5,55, indicating the sensitivity of profit to changes in sales volume. The analysis of costs, volume, profit, BEP, and planning business strategies for profitibility, emphasizing the importance of an analytical approach. The limitations of assumption data and time coverage suggest further research with broader empirical data and considering external factors.